Soil and Water Conservation - Need for Better Management in the Country - Tiwari, K. M. (Indian Forester, 1983)
Efficient land use management policy could go a long way in our efforts towards removal of poverty in the country. Agricultural productivity from our land has not been able to keep pace with the constantly increasing population of the country. Merely diverting forest areas to agriculture would not solve the problem, and it is imperative that production per ha of agriculture crops be increased. Pre-requisite for this is our efficient conservation of soil and water resources of the country. Looking at the present situation it seems that an adequate attention to soil and water conservation measures in managing our agricultural lands has not been paid. Forest is the foster mother of agriculture and increasing the forest area in the watersheds of our important river systems would definitely help in an increased agricultural productivity of the country.